2004
DOI: 10.1099/ijs.0.63074-0
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia araoensis sp. nov. and Nocardia pneumoniae sp. nov., isolated from patients in Japan

Abstract: Two actinomycete strains isolated from two patients with lung nocardiosis between 1995 and 1997 in Japan were assigned to novel species of the genus Nocardia based on morphological and chemical criteria. Comparative 16S rRNA gene sequence analysis of the two strains revealed that they belong to the genus Nocardia and are most closely related to the species Nocardia beijingensis. Determination of DNA–DNA relatedness indicated that these strains could be assigned to two novel species. Based on their phenotypic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…This is partly due to the discrepancy between the manufacturers' recommendations and the findings of Biehle et al, who demonstrated an ϳ1-log 10 -dilution-lower inoculum size when using the recommended 0.5 MacFarland suspension (2). Major taxonomic revisions have occurred within the last 10 years, further complicating the comparison of studies (7,11,12,21). With potentially important clinical and epidemiological differences between species, it is important to identify isolates to the species level as accurately and rapidly as possible.…”
mentioning
confidence: 53%
“…This is partly due to the discrepancy between the manufacturers' recommendations and the findings of Biehle et al, who demonstrated an ϳ1-log 10 -dilution-lower inoculum size when using the recommended 0.5 MacFarland suspension (2). Major taxonomic revisions have occurred within the last 10 years, further complicating the comparison of studies (7,11,12,21). With potentially important clinical and epidemiological differences between species, it is important to identify isolates to the species level as accurately and rapidly as possible.…”
mentioning
confidence: 53%
“…Since that time, several of the new species are represented by only one strain or a few strains, so their occurrence in humans still has to be assessed (6,8,11,12,17,28).…”
Section: Discussionmentioning
confidence: 99%
“…Not all of them have been found in humans, and Nocardia asteroides, previously most frequently isolated from clinical specimens, has proved to be heterogeneous and has been divided into several species (18). More recently, additional species of human origin have been described (6,8,9,11,12,17,28).…”
mentioning
confidence: 99%
“…In 1995, Steingrube et al described an RFLP method for identification of 12 species and taxa of Nocardia, including N. nova, based on a prior study by Lungu and colleagues (131) and using mycobacterial primers developed by Telenti et al (181,186 98.0% similarity to the N. nova type strain, suggesting that some isolates considered to belong to N. nova by hsp65 PRA and antibiotic susceptibility may actually belong to other, unrecognized species (43).…”
Section: Nocardia Novamentioning
confidence: 99%